1994
DOI: 10.1002/neu.480250702
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic agents prevent motoneuron death following sciatic nerve section in the neonatal mouse

Abstract: We have examined the ability of different neurotrophic and growth factors to prevent axotomy-induced motoneuron cell death in the developing mouse spinal cord. After postnatal unilateral section of the mouse sciatic nerve, most motoneuron (MN) loss occurs in the lateral motor column of the fourth lumbar segment (L4). Significant axotomy-induced cell death occurred after surgery performed on or before postnatal day (PN) 5. In contrast, no significant cell loss was found when axotomy was performed after PN10. Ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
153
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(160 citation statements)
references
References 44 publications
7
153
0
Order By: Relevance
“…Limb bud ablation (i.e., lack of target tissue) and deafferentation experiments, using developing chicks, have shown a rescue of MANs through administration of exogenous neurotrophin Qin-Wei et al, 1994). Similar studies have also been carried out using adult mammals showing a rescue of almost all MNs in the L4 SC after axotomy of the sciatic nerve Li et al, 1994). However, a recent study published by our laboratory was the first to complete an in vivo investigation into the effects of a single neurotrophin, BDNF, on the survival of subpopulations of MANs during EPCD in developing mammals.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…Limb bud ablation (i.e., lack of target tissue) and deafferentation experiments, using developing chicks, have shown a rescue of MANs through administration of exogenous neurotrophin Qin-Wei et al, 1994). Similar studies have also been carried out using adult mammals showing a rescue of almost all MNs in the L4 SC after axotomy of the sciatic nerve Li et al, 1994). However, a recent study published by our laboratory was the first to complete an in vivo investigation into the effects of a single neurotrophin, BDNF, on the survival of subpopulations of MANs during EPCD in developing mammals.…”
Section: Introductionsupporting
confidence: 55%
“…Neurotrophin-3 knockout experiments have noted no loss of MNs in the LMC and MMC (Yan et al, 1993;Snider, 1994;Huang and Reichardt, 2001;Patel et al, 2003) and facial motor nucleus neuron loss is shown to be nonsignificant, i.e., no obvious deficits were detected, in the brainstem of newborn NT-3Ϫ/Ϫ mice . Whereas certain in vitro studies have demonstrated inadequate promotion of chick motoneuron survival through the use of NT-3 and BDNF, the application of these same neurotrophic factors on cultured fetal rat motoneurons demonstrated a survival-promoting effect for these agents (reviewed in Li et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of neurotrophins in preventing the inappropriate paring of synaptic connections in perinatal animals leaves these neurons much more susceptible to cell death following the removal of a trophic source, either through biochemical manipulations or via de-efferentation by axotomy, than neurons in adult animals [76,77]. Sciatic lesion in neonatal mice results in a loss of approximately two-thirds of the lower motor neurons in the lumbar enlargement, which is completely ameliorated with the application of BDNF, NT-3, or insulin-like growth factor I (IGF-I) [78]. This death of neonatal motor neurons is in stark contrast to lower motor neurons that not only survive, but regenerate following adult sciatic nerve injury; sciatic injury has been shown to result in increased NGF, BDNF, IGFs, cilliary neurotrophic factor, and glial-derived neurotrophic factor secretion from Schwann cells [44][45][46][47][48][49][50][51][52][53].…”
Section: Neurotrophins Development and Survivalmentioning
confidence: 99%